Blood transfusion and Jehovah's Witnesses - Monica Vieira da Motta Piacsek; Marcia Vieira da Motta; Ricardo Nusralla Haddad (Universidade de Sao Paulo, 2018)
Brazilian physicians and judges frequently have to decide whether to save the life of a Jehovah Witness patient that refuses blood transfusion or let the patient die when treatment refusal reflects their religious belief. The Penal Code condemns the physician who fails to use all the available means to save the patient. The Civil Code, contrarily, requires the professional to respect the patient's autonomy regarding their decision over an intervention with potential risk of death. The Brazilian Constitution guarantees religious freedom and the inviolability of the right to life. This article reviews the Brazilian jurisprudence on the matter through recovery of all available decisions in the Federal and State Courts' online database up to 2013. The results show that these superior courts consider that people are not allowed to let go of their own lives for religious reasons when in a state of "imminent death". However, when the patient's clinical state is qualified as "at risk of dying", physicians are requested to respect their dissent.